Upah Berkeadi lan Ditin jau dari P erspektif Islam - Waliam, Armansyah (Universitas Islam Negeri Sunan Kudus, 2017)
This study is motivated by the popular use of human power in human civilization and in accordance with its nature as a creature of god that needs each other. The need for more manpower to spur the growth of production that ultimately the utilization of human labor is identical to the work and wages provided by the company. While the government sees wages, on the one hand to ensure the fulfillment of a decent life for workers and their families, increases employee productivity and increases people’s purchasing power, on the other hand to promote business progress and competitiveness. This study uses a qualitative approach with literary research nuances. The study also aims to provide answers to wage polemics, in which workers hold that wages are a source of income to meet the needs of himself and family and a reflection of job satisfaction. It is therefore necessary to provide salary or wage solutions in Islamic perspective. The results of this study indicate that wages in Islam are compensation received by workers for the benefits of work done properly and correctly, in the form of material and reward based on the principles of al-’adl and morals with respect to humanity aspect. Based on the principle of justice and morals, the excess wages in Islam is closely related to the principle of morality that is able to meet basic needs, education, and health security well and honorable, so that wages are not only limited to mere material (dimension of the world) but penetrate the limits of life, the dimension akherat .